A case study of delexical nouns in an EFL setting - Ruzana Galstyan-Sargsyan; Oksana Polyakova (Moderna Språk)
This paper demonstrates the relevance of delexical nouns (way, end, case and point) based on corpus findings, course book analyses and classroom experiments. To this end, first, delexical noun functions and frequencies have been studied in-depth in two large English language corpora: Corpus of Contemporary American English (COCA) and British National Corpus (BNC). Additionally, the study reviewed the compound nouns' dictionary meanings. Two coursebooks, namely New English File and Face2Face, have been investigated to determine if delexical nouns are addressed in English language coursebooks to provide ideas to guide the learners in the classroom. Finally, a data-driven learning (DDL) experiment was carried out to assess the participants’ familiarity with the delexical nouns and their collocations. The results of the quantitative analysis from the study demonstrate that delexical nouns are introduced in the course books but are not explicitly explained. Consequently, there are no actual exercises to practise them. The classroom experiment findings reveal the participants’ positive attitude towards how the four delexical nouns, way, end, case and point, were introduced and taught.